PEMANFAATAN ARANG AKTIF SABUT KELAPA SAWIT SEBAGAI ADSOBEN ZAT WARNA SINTETIS REACTIVE RED-120 DAN DIRECT GREEN -26 - Melfi Puspita; M. Lutfi Firdaus; Nurhamidah Nurhamidah (ALOTROP, 2017)
The problem of environmental polution caused by waste of batik industry lately is increasing, so it needed a method to overcome that problem. The aim of this study was to determine the ability of activated charcoal from coconut fiber palm in adsorbing Reactive Red-120 and Direct Green-26 dyes in waste of batik along with determining the parameters of isotherms adsorption using UV-Vis Spectrophotometer analysis method. Variations of pH, contact time, adsorbent weight and temperature were carried out as variable to obtain optimum conditions of the adsorption process. The optimum of conditions for Reactive Red-120  occured at pH 3 and a contact time of 30 minutes, while Direct Green-26  occurred at pH 4 and a contact time of 40 minutes, with each adsorbent weight 150 mg and the temperature 30 °C. Adsorption isotherms determined by Freundlich and Langmuir models with maximum adsorption capacity (Qmax) were obtained for the Reactive Red-120  was 400 mg/g, while Direct Green-26 is 169 mg/g.